An approach for 3D visualization of discrete event simulation - Zhong, Yongmin; Shirinzadeh, B. (ASME, 2004)
This paper presents a new approach to create 3D visualization from discrete simulation results. This approach connects discrete event simulation directly to 3D animation with its novel methods of analyzing and converting discrete simulation results into animation events to trigger 3D animation. In addition, it constructs a 3D animation framework for the visualization of discrete simulation results. This framework supports the reuse of both the existing 3D animation objects and behavior components, and allows the rapid development of new 3D animation objects by users with no special knowledge in computer graphics but average computer skills. This approach has been implemented with the software component technology, and successfully applied in industry. Results from its practice in an electronics assembly factory are also provided in the paper to demonstrate the performance of this new approach.